Assessment of disease impact through health‐related quality of life measurement in primary progressive aphasia - Thomas Hopkins; Eunbi Kwon; Allison Lapins; Nathan Gill; Angela Roberts; Emily Rogalski (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract INTRODUCTION Measurements of health‐related quality of life (HRQoL) are important for capturing disease impact beyond physical health and relative to other diseases but have rarely been assessed in primary progressive aphasia (PPA). METHODS HRQoL was characterized overall, by sex and subtype in PPA (n = 118) using the Health Utilities Index‐2/3 (HUI2/3). Multiple linear regression assessed associations between HRQoL and language severity. RESULTS Multi‐attribute HUI2/3 summary scores indicated moderate to severe impairment. Scores did not differ by sex and were more severe for semantic than non‐semantic PPA. Language severity scores showed significant associations with HUI multi‐attribute scores and select single‐attribute measures (hearing, sensation, cognition, and speech) with less language impairment associated with better functional capacity related to HRQoL. DISCUSSION This study identified poor HRQoL in a relatively large PPA cohort. HRQoL measures aid in determining patient perspective, policy decision making, and resource allocation. Results may be used to advocate for PPA support. Highlights Primary progressive aphasia (PPA) negatively impacts health‐related quality of life. Health utilities index scores are associated with Western Aphasia Battery performance in PPA. Severity of language impairment in PPA is associated with poorer quality of life.